Exercise and pregnancy - review of literature and current recommendations - Kuźniar, Aleksandra; Wąsiewicz, Edward; Szawica, Dominik; Fularska, Kamila; Oleszko, Michał (Journal of Education, Health and Sport, 2023)
Introduction: Regular physical activity benefits everyone, regardless of age, considering individual abilities and health conditions. Pregnancy is a special time for women as well as an appropriate time to reassess lifestyle choices and introduce better habits. Aim of the study: Summary of the current state of knowledge about exercise in pregnancy, recommended forms of physical activity and benefits for health and well-being. Methods and Materials: A review was conducted in PubMed, ScienceDirect and GoogleScholar including publications from the last 5 years. Literature was searched using the following terms: “physical activity”, “exercise”, “pregnancy”, “resistance exercise”, “aerobic exercise”. Results: The number of studies focused on benefits of prenatal exercise is escalating. It has been proven that physical activity can prevent gestational diabetes, help in blood glucose, and blood pressure control, improve the mental state of a mother, and contribute to the improvement of placental function. It can also affect a parturition and child postnatal development. At the same time, it turned out that many women do not have the appropriate knowledge and do not undertake the recommended activity during pregnancy. Conclusion: Interest in the topic of physical activity during pregnancy has increased significantly in recent years, yet further research is needed to dispel the existing doubts and to understand thoroughly the significance of physical activity during pregnancy on maternal and child health. Future educational interventions aimed at pregnant women in terms of safety and recommended forms of activity during pregnancy are necessary to update their knowledge and to help them implement recommendations.